Level Straight Accelerated Flights (Advances in Military Technology, 2022)
The paper introduces the analytical method derivation for flight time and flight path length in horizontal straight flight. An airplane is considered to be the mass point. Aerodynamic characteristics of the airplane are replaced by the parabolic polar curve. Engine thrust does not change with flight speed. Working formulas are determined on the base of the analytical integration of the airplane motion equation. All solutions are performed in general dimensionless shape. Determination of the real airplane characteristics requires knowledge of the optimum airspeed at operation conditions.
Keywords: level straight flight; equation of motion; flight performance; optimum airspeed